Tracking animal identity - Jackson, Tom (North Mankato, MN Capstone Press, a Capstone imprint, 2016)
Describes the technology that is used to track the identity of animals, including recording sounds, monitoring tree damage, DNA analysis, and carbon dating fossil finds
The World Around us
1 2 13 15
Keywords: Animal behavior -- Juvenile literature; Animals -- Identification -- Juvenile literature; Tracking and trailing -- Juvenile literature